STUDIES ON THE EFFECT OF CILOSTAZOL ON THE PROSTAGLANDINS PRODUCTION DURING ADP-INDUCED PLATELET AGGREGATION WITH ENDOTHELIAL CELLS - Chijiwa, T; Shiragiku, T; Kato, S; Igawa, T; Kimura, Y (Thrombosis and Haemostasis, 1987)
It has been clinically reported that cilostazol has a potent inhibitory effect on platelet aggregation without changing the prostacyclin level. This study was undertaken to elucidate this clinical effect by a technique developed by us in which platelet aggregation could be evaluated in the presence of cultured endothelial cells. Human umbililical cord vein endothelial cells (HUVEC) were coated (cultured for a few days supplemented with 10% fetal claf serum) on the inner surface of glass cuvette, and platelet aggregation was traced by the stimulation of citrated-PRP with 7.5 μM ADP in this cuvette. The 6-keto-prostaglandin F1α (6-k-PGF) and thromboxane B2 (TXB) produced in the supernatant of the stimulated PRP were measured by radioimmunoassay (Amersham). The cyclic adenosine monophosphate (cAMP) level in platelets and HUVEC was measured by radioimmunoassay (YAMASA). Cilostazol showed a potent inhibitory effect on platelet aggregation in the presence of HUVEC by the suppresion of TXB production, but not by the suppression of 6-k-PGF production. Cilostazol stimulated cAMP production in both platelets and HUVEC. On the other hand, aspirin also showed an inhibitory effect on platelet aggregation in the presence of HUVEC, but suppressed production of both TXB and 6-k-PGF.As a result, the clinical effect of cilostazol was confirmed by the fact that TXA2 production in a platelet/HUVEC coexisting system was specifically suppressed.